Romosozumab Followed by Antiresorptive Treatment Increases the Probability of Achieving Bone Mineral Density Treatment Goals. (6th October 2021) - Cosman, Felicia; Libanati, Cesar; Deignan, Cynthia; Yu, Zhigang; Wang, Zhenxun; Ferrari, Serge; Beck Jensen, Jens‐Erik; Peris, Pilar; Bertoldo, Francesco; Lespessailles, Eric; Hesse, Eric; Cummings, Steven R
ABSTRACT: Increases in bone mineral density (BMD) with osteoporosis treatment are associated with reduced fracture risk. Increasing BMD is therefore a goal of osteoporosis therapy. Here, we compare the probability of achieving a T ‐score of > −2.5 over 3 years at the total hip (TH) or lumbar spine (LS) in women with osteoporosis, ≥55 years of age, after the following treatment sequences: 1 year romosozumab followed by 2 years denosumab (FRAME and FRAME extension trials), 1 year romosozumab followed by 2 years alendronate, or alendronate‐only for 3 years (ARCH trial). Probabilities of attaining the BMD target within 1 year of treatment were also determined. At both skeletal sites, in women with a baseline T score ≥ −2.7, there was >50% probability of achieving the BMD target with any 3‐year regimen. The probability of achieving the target BMD in those with a baseline TH T score equal to −3.0 was 61% with romosozumab/denosumab, 38% with romosozumab/alendronate, and 9% with alendronate. In those with a baseline LS T score equal to −3.0, the probability of achieving a T ‐score > −2.5 was 93% with romosozumab/denosumab, 81% with romosozumab/alendronate, and 55% with alendronate. With 1 year of treatment, in patients with a baseline TH T ‐score equal to −2.7, the probability of reaching the target T score with romosozumab was 71% to 78% and 38% with alendronate. For patients with an initial LS T ‐score equal to −3.0, the probability of achieving the target T ‐score over 1 year was 85% to 86% with romosozumab and 25% for alendronate. Our findings suggest baseline BMD and the probability of achieving BMD T ‐score goals are factors to consider when selecting initial treatment for patients with osteoporosis. As baseline T ‐score falls below −2.7 (TH) and −3.0 (LS), alendronate has <50% likelihood of achieving a BMD goal above osteoporosis range, whereas these probabilities remain relatively high for regimens beginning with romosozumab. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.